Peptide and Amino Acids Separation and Identification from Natural Products - Neda, on; Vlazan, Paulina; Pop, Raluca Oana; Sfarloaga, Paula; Grozescu, Ioan; Segneanu, Adina-Elena (IntechOpen, 2012)
None